King John - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1997)
"King John" by William Shakespeare is a history play written in the mid-1590s about the turbulent reign of King John of England. The play follows John's struggle to maintain his throne against French invasion, papal excommunication, and challenges from his nephew Arthur's claim to the crown. As political alliances shift and betrayals mount, John faces external enemies and internal rebellion from his own nobles. Through battles, diplomatic marriages, and religious conflict, Shakespeare dramatizes a king's desperate fight for legitimacy and power during one of England's most unstable periods. (This is an automatically generated summary.)
The First Folio, 1623
Wikipedia page about this book: https://en.wikipedia.org/wiki/King_John_(play)
Release date is 1997-11-01
Keywords: John, King of England, 1167-1216 -- Drama; Great Britain -- History -- John, 1199-1216 -- Drama